PENGARUH BRAND EQUITY, KUALITAS PRODUK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN TAS MEREK EIGER - Syihabudin, Ahmad; Subagyo, Subagyo; Widodo, Moch. Wahyu (Universitas Nusantara PGRI Kediri, 2022)
This study aims to determine the effect of brand equity, product quality, lifestyle, either partially or simultaneously on the purchasing decisions of Eiger bags at Universitan Nusantara PGRI Kediri students. This study uses a quantitative approach and is a causal relationship research. The population in this study were all active students of the Nusantara University, PGRI Kediri. The sample was determined by 40 students who were taken using purposive sampling technique. Data collection techniques using questionnaires and data analysis used in this study multiple linear regression analysis. The results of the study show that product quality has a significant effect on purchasing decisions while brand equity and lifestyle have no significant effect on purchasing decisions for Eiger products at Nusantara University students, PGRI Kediri, while simultaneously brand equity, product quality, and lifestyle have a significant effect on product purchasing decisions. Eiger at Nusantara University students, PGRI Kediri.